Il conflitto in Casamance (Senegal) come merce di scambio nel baratto geopolitico regionale per il controllo delle risorse - Serrenti, Maria (L'Uomo Società tradizione sviluppo, 2022)
Casamance, Southern region of Senegal, has been suffering a conflict of "low intensity" since 1982, when the separatist Mouvement des Forces Démocratiques de la Casamance (MFDC) started an armed struggle for independence. After a period of fragile calmness, following the peace agreements in 2004, the region has been caught in an alternate state between war and peace, hostage of a new escalation of violence. Separatism in Casamance is not just a spot of bother of the Government but also an important geopolitical card played in other and more important issues: from the exploitation of offshore oil and fish resources along the border with Guinea-Bissau to its role of "democratic power" passing through the internal political struggles. After the landslide defeat of President Wadès coalition “Soopi” at the last regional election in 2009, the Casamance dossier could play again a major role in the struggle for power in the upcoming presidential election in 2013.